War, Crime, Victimology, Human Rights and Criminal Justice Holistic Approach - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Kharkiv : Pravo, 2024)
International and national substantial criminal law protects human rights and maintains a balance between people’s security and the state’s apparatus. New hybrid and aggressive war challenges necessitate understanding the stability of criminal legal form and social care amidst evolving public and social relations. By analyzing crime and abuse of power tendencies, we can challenge social control schemes related to international society, the state, perpetrators, victims, and civil society attitudes. This article explores the interrelationships among war consequences, crime, modern victimology, human rights, and criminal justice, using a holistic approach grounded in human rights discourse. It highlights the integration of international and national means within modern criminal justice to safeguard victims from crime and abuse of power at individual and collective levels. The article particularly focuses on the interplay between war and crime, fragmentation of international criminal law, victims’ reparations, and criminal policy development. Міжнародне та національне матеріальне кримінальне право захищає права людини та підтримує баланс між безпекою людей і державним апаратом. Нові виклики гібридної та агресивної війни вимагають розуміння стабільності кримінально-правової форми та соціальної опіки в умовах еволюції суспільних і соціальних відносин. Аналізуючи тенденції злочинності та зловживання владою, ми можемо кинути виклик схемам соціального контролю, пов’язаним із міжнародним суспільством, державою, злочинцями, жертвами та ставленням громадянського суспільства. У цій статті досліджуються взаємозв’язки між наслідками війни, злочинністю, сучасною віктимологією, правами людини та кримінальним правосуддям, використовуючи цілісний підхід, заснований на правозахисному дискурсі. Він підкреслює інтеграцію міжнародних і національних засобів у сучасне кримінальне правосуддя для захисту жертв від злочинів і зловживання владою на індивідуальному та колективному рівнях. Стаття особливо зосереджується на взаємозв’язку між війною та злочинністю, фрагментації міжнародного кримінального права, відшкодуванні жертвам і розвитку кримінальної політики.
Tuliakov V. O. War, Crime, Victimology, Human Rights and Criminal Justice Holistic Approach / V. O. Tuliakov // Yearbook of Ukrainian law : Coll. of scientific papers / responsible for the issue Ye. A. Hetman. – Kharkiv : Pravo, 2024. – № 16. – Р. 265-280. Режим доступу: https://hdl.handle.net/11300/28573
Keywords: security; penal law; victim; human rights; war; crime; holistic approach; безпека; кримінальне право; жертва; права людини; війна; злочин; холістичний підхід